SOME THOUGHTS ABOUT THE PLACE, CONTENT AND NATURE OF THE MEDIA IN THE PRESENT TIME (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The article provides information on the content and functions of the mass media in the education of young people. At the same time, it is said that the mass media is an important factor for the socialization of the individual, it is important to show the place and role of the mass media in the process of deepening reforms and building a renewed society in Uzbekistan, and it has important theoretical and practical methodological significance.